A good place to do time? Detailing the construction of symbolic social boundaries in correctional boot camps - Schultz, William; Bucerius, Sandra M.; Haggerty, Kevin D. (My University, 2024)
Drawing on qualitative interviews with 51 incarcerated adult men and nine correctional officers in a Western Canadian prison system, we ask why some incarcerated people find it appealing to be placed on correctional boot camp units and what such appeals tell us about broader conditions of incarceration. Participants on three boot camp units drew on narratives relating to (a) extrinsic benefits, (b) discipline and structure, (c) teamwork and positive relationships, and (d) an opportunity for self-improvement to construct symbolic boundaries between “normal” units and boot camps, as well as their former self and their transformed current self. By drawing symbolic boundaries between the past and present and between other units and their boot camp unit, our participants create narratives that allow them to partially mitigate some pains of imprisonment.
Keywords: prison; boot camps; correctional programming; boundary work; prison subcultures